Porous Materials to Support Bilayer Lipid Membranes for Ion Channel Biosensors - Thai Phung; Yanli Zhang; James Dunlop; Julie E. Dalziel (International Journal of Electrochemistry)
To identify materials suitable as membrane supports for ion channel biosensors, six filter materials of varying hydrophobicity, tortuosity, and thickness were examined for their ability to support bilayer lipid membranes as determined by electrical impedance spectroscopy. Bilayers supported by hydrophobic materials (PTFE, polycarbonate, nylon, and silanised silver) had optimal resistance (14–19 GΩ) and capacitance (0.8–1.6 μF) values whereas those with low hydrophobicity did not form BLMs (PVDF) or were short-lived (unsilanised silver). The ability of ion channels to function in BLMs was assessed using a method recently reported to improve the efficiency of proteoliposome incorporation into PTFE-supported bilayers. Voltage-gated sodium channel activation by veratridine and inhibition by saxitoxin showed activity for PTFE, nylon, and silanised silver, but not polycarbonate. Bilayers on thicker, more tortuous, and hydrophobic materials produced higher current levels. Bilayers that self-assembled on PTFE filters were the longest lived and produced the most channel activity using this method.